The effect of authentic leadership and transparent organizational communication on employee welfare with mediation variables of employee trust in medium companies; El efecto del liderazgo auténtico y la comunicación organizacional transparente en el bienestar de los empleados con variables mediadoras de la confianza de los empleados en empresas medianas - Wisnu Yuwono; Daniel Danito; Ferdinand Nainggolan (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
The employee turnover rate in the industrial world has increased sharply, especially in medium-sized companies. This turnover rate is closely related to employee psychological welfare. This study aims to analyze the effect of authentic leadership variables and transparent organizational communication on employee welfare mediated by employee trust in medium-sized companies. The sample in this study amounted to 150 employees who work in medium-sized companies in the city of Batam City, Indonesia Country. Through data analysis with the help of the SmartPLS version of 3.0, it is shown that all the variables tested in this research model have a significant effect, both direct and indirect. That to improve the psychological well-being of employees optimally, authentic leadership variables and transparent organizational communication must go through employee trust as a mediating variable. The results of this study can be used as a reference by the manager of medium-sized business group companies in Batam in designing matters relating to the welfare of their employees.
Keywords: D22; D23; I31; 330; authentic leadership; transparent organizational communication; employee's trust; employee's well-being